Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592